2009
DOI: 10.1902/jop.2009.090159
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Antioxidants in Patients With Type 1 or 2 Diabetes and Inflammatory Periodontal Disease: A Case‐Control Study

Abstract: The decrease in salivary reduced-glutathione levels in patients with type 1 DM may have a role in periodontal tissue destruction by predisposing tissues to oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 33 publications
5
42
1
Order By: Relevance
“…The mean total salivary antioxidant capacity of the present cohort at baseline was 2083 U.Carr which resulted higher than normal range thus denoting a potential state of inflammation in diabetic patients affected by moderate periodontitis. The over-production of free radicals caused by periodontal inflammation is in fact supposed to cause an up-regulation of the anti-oxidant defence [25,26]. The results of the present study agree with literature relating high levels of salivary antioxidants (SAT) to a possible periodontal inflammatory condition.…”
Section: Number Of Dm-2 38supporting
confidence: 90%
“…The mean total salivary antioxidant capacity of the present cohort at baseline was 2083 U.Carr which resulted higher than normal range thus denoting a potential state of inflammation in diabetic patients affected by moderate periodontitis. The over-production of free radicals caused by periodontal inflammation is in fact supposed to cause an up-regulation of the anti-oxidant defence [25,26]. The results of the present study agree with literature relating high levels of salivary antioxidants (SAT) to a possible periodontal inflammatory condition.…”
Section: Number Of Dm-2 38supporting
confidence: 90%
“…14,15 Furthermore, the antioxidant profile of this biological fluid has been investigated in others studies. [16][17][18][19] Since antioxidant levels may vary in different organs and tissues of patients with DS, we hypothesized that this vulnerability to oxidative stress can also be observed in saliva. Studies investigating antioxidant levels and biomarkers of oxidative damage in saliva of patients with DS are scarce and the results regarding the use of sialochemistry to explain the role of saliva in oral health and well-being of these patients are contradictory.…”
Section: Introductionmentioning
confidence: 99%
“…(23). Our previous study (24) identified GSH activity in serum and saliva of patients with type 2 diabetes which was significantly low when compared with control group.…”
Section: Alteration In Glutathione Metabolismmentioning
confidence: 95%